Evaluation of secondary metabolites of Phoma sp. Test strain # 54 (FGCCW) for management of Parthenium hysterophorus - A.K. PANDEY, SADAF QUERESHI* and (Indian Phytopathology, 2007)
Herbicidal potential of Cell free culture filtrate (CFCF) of Phoma sp. FGCCW#54 against Parthenium hysterophorus was evaluated by shoot cut, seedling and detached leaf bioassays. Maximum mortalities of shoots, seedlings and phytotoxic damage was obtained from 21 days old cell free culture filtrate (CFCF) at 100% concentration. Significant reduction in biological contents i.e. photosynthetic pigment and protein was observed in the host weed on treatment with the CFCF as determined by Detached leaf bioassay. Phytotoxic damage such as severe wilting, chlorosis, necrosis and complete collapse of the entire parts of the weed were also noticed due to CFCF application. Maximum leaf area damage occurred in detached leaves of the test weed with 100% concentration of 21 days old fermented broth after 24 hours post treatment (hpt).